Reliability and construct validity of knowledge, attitude, and practice of medical doctors on smoking cessation guidelines - Shalihin, Mohd Shaiful Ehsan; Md Aris, Mohd Aznan; Mohd Rus, Razman; Nik Mohamed, Mohamad Haniki; Jamani, Nurjasmine Aida (Kulliyyah of Medicine, IIUM, 2017)
Introduction: Islam forbids any forms of tobacco smoking. Prevalence of active smokers in Malaysia is increasing despite availability of stop-smoking clinics. Thus, the practice of healthcare professionals involved in providing smoking cessation intervention needs to be assessed using validated assessment tool.